(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Chronic (neglected) radiocapitellar joint dislocation is one of the feared complications of Monteggia fractures especially when associated with subtle fracture of the ulna bone. Many treatment strategies have been described to manage chronic Monteggia fracture and the need for annular ligament reconstruction is not always clear. The purpose of this study is to highlight the operative management of missed Monteggia fracture dislocation and to achieve excellent results rather to delay the treatment and later on facing more complication in the form of deformity and loss of movements. Ten patients with an average of 3 months old fracture dislocation were included in the study. Results were evaluated according to the Kims Criteria. Open reduction and internal fixation with plate and screws of the forearm bones and relocation of radial head was done. Radial head was kept located at its position with the help of K wire for 6 weeks